2017
DOI: 10.3390/ijms18020344
|View full text |Cite
|
Sign up to set email alerts
|

Rett Syndrome: A Focus on Gut Microbiota

Abstract: Rett syndrome (RTT) is an X-linked neurodevelopmental disorder affecting 1 in 10,000 live female births. Changes in microbiota composition, as observed in other neurological disorders such as autism spectrum disorders, may account for several symptoms typically associated with RTT. We studied the relationship between disease phenotypes and microbiome by analyzing diet, gut microbiota, and short-chain fatty acid (SCFA) production. We enrolled eight RTT patients and 10 age- and sex-matched healthy women, all wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 64 publications
8
78
0
Order By: Relevance
“…Increasing evidence suggests that the gut microbiota can affect the symptoms of intellectual disability (ID) and autism spectrum disorder (ASD) diseases (Borghi et al, 2017;Caracciolo et al, 2014;Mayer et al, 2014). It is clear that host genes influence the composition of gut microbiota (Wang et al, 2016;Snijders et al, 2016), but the molecular mechanisms that regulate hostcommensal microbiota homeostasis in normal and disease states remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests that the gut microbiota can affect the symptoms of intellectual disability (ID) and autism spectrum disorder (ASD) diseases (Borghi et al, 2017;Caracciolo et al, 2014;Mayer et al, 2014). It is clear that host genes influence the composition of gut microbiota (Wang et al, 2016;Snijders et al, 2016), but the molecular mechanisms that regulate hostcommensal microbiota homeostasis in normal and disease states remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing reads were processed, filtered and analysed following similar procedures described in Borghi et al [48]. Briefly, read pairs were merged together by PandaSeq software [49] discarding fragments of length <300 bases or >900 bases, as well as non-overlapping sequences.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, some microorganisms, such as bacteroides or Clostridia members, are able to produce BCFAs from the proteolytic metabolism of branched-chain amino acids. The higher levels of Bacteroidaceae or Peptostreptococcaceae observed in the HFHC group could be related to the higher levels of BCFAs observed, as found in other diseases related to the gut-brain axis, such as obesity [65], Rett syndrome [66], or anorexia nervosa [67]. On the other hand, there is evidence in mice that acetate can alter the levels of glutamate, glutamine, and GABA [68], and some studies have shown that SCFAs and their metabolites can stimulate vagus nerve signaling [69,70].…”
Section: Discussionmentioning
confidence: 99%